THE USE OF DIGITAL TECHNOLOGY IN INFORMAL ENGLISH LANGUAGE LEARNING: HOW THE PRACTICES SUPPORT LEARNING OUTCOMES? - Laila Thahira Rahman; Nurhandayani Supraptiningsih; Septia Kusumaning Pratiwi; Asha Maharani Nupus (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Informal digital learning of English (IDLE) is Benson’s conceptual framework that refer to the context where English language learners learn English, in which they can learn the language beyond classroom. The framework can be applied with any digital media. The present study was conducted by means of surveys and open-ended questions to investigate how students in an Islamic university in Jakarta used digital technology and how it supported their English learning outcome. The survey of the use of digital devices for English learning was adapted, and the open- ended questions were developed to find out more information about the way how they use the digital tools beyond classroom English learning activities. To analyze the data, descriptive quantitative and thematic analysis were employed. And the results show that several digital applications were used by the students of teacher training education faculty to help them learn English vocabulary and the way how they used them were discussed.